2012
DOI: 10.20965/jdr.2012.p0037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Volcanic Activity at Sinabung Volcano, After More Than 400 Years of Quiet

Abstract: Before its 2010 eruption, Sinabung Volcano was a Btype volcano, in its Indonesian classification. A series of explosions featuring 1-5 km high phreatic-ash columns occurred from August 27, 2010 untill September 7, 2010. SO2 flux measured during the eruptions showed sizeable gas emission and the youngest volcanic product has age of 1200 years BP obtained from 14C dating. At the end of August 2010, four continuous seismic stations were established around the volcano, and 6 additional stations were deployed in Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…1 showed the characteristic results of silica gel having composition O 39.74 %, Na 1.08 %, Al 6.21 % and Cl 1.01%. The results of EDX analysis also showed that the purity of silica gel was 51.96 % which is almost found similar as reported by Hendrasto et al [8] that volcanic ash of Sinabung mountain contained 57. 01 % silica.…”
Section: Resultssupporting
confidence: 87%
“…1 showed the characteristic results of silica gel having composition O 39.74 %, Na 1.08 %, Al 6.21 % and Cl 1.01%. The results of EDX analysis also showed that the purity of silica gel was 51.96 % which is almost found similar as reported by Hendrasto et al [8] that volcanic ash of Sinabung mountain contained 57. 01 % silica.…”
Section: Resultssupporting
confidence: 87%
“…At the beginning of the eruption around the end of 2009 (Figure 3) up to August 2010 (Figure 4), the activity of Sinabung volcano, which has been inactive for a long time (more than 400 years) shocked the local residents, even though the height of the volcanic ash column was only around 2900 m. After the 2010 eruption, the volcano returned to a dormant stage for two years before erupting again in mid-September 2013, with the height of the volcanic ash column nearly doubling that of the 2010 explosion, at around 5000 m (Hendrasto et al, 2012). The use of high-resolution imagery produced more in-depth analysis in monitoring the direction, pattern, and movement of the Sinabung pyroclastic material (Kadavi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to 2010, Sinabung was classified by the Center for Volcanology and Geological Hazard Mitigation (PVMBG) as a "B-type" volcano, which has not erupted in modern history since 1600 AD (1) .The first sign of increased Sinabung activity in the peak area, was detected with interferometric synthetic aperture radar during the period 2007-2010 (2) (3). Sinabung experienced a phreatic eruption-the first confirmed eruption in a historic time (1)(4) (5). Sulfur dioxide emissions were detected by the Aura/Ozon Mapping Instrument on August 27, 2010.…”
Section: Introductionmentioning
confidence: 99%